1920 kot leto intenzivnih prizadevanj za volilno pravico žensk - Selišnik, Irena (Studia Historica Slovenica, 2023)
In the article we will focus on key demand of the first wave of the women’s movement, on the women’s right to vote in the Slovenian part of the Kingdom of Serbs, Croats and Slovenes. With the establishment of the new state multiple legislation drafts and proposals for women’s suffrage were created in Provincial Government for Slovenia. We would be interested in political parties and their different approaches to solve the question and how in this framework women’s movement was engaged. Especially in 1920 numerous associations organized collective actions for suffrage through petitions, calls, media articles, in this framework particularly Slovenska ljudska stranka was active.
Keywords: 1920; demonstracije; demonstrations; election; gender; interwar period; Kraljevina Srbov, Hrvatov in Slovencev; medvojno obdobje; political parties; politične stranke; spol; volilna pravica žensk; volitve; women’s associations; women’s right to vote; Zgodovina; ženske